The effects of warm-up on intermittent sprint performance in a hot and humid environment - Yaicharoen, P.; Wallman, K.; Morton, A.; Bishop, D.; Grove, R. J. (Journal of Sports Sciences, 2012)
It is unknown whether a passive warm-up or an active warm-up performed at an intensity based on lactate thresholds could improve prolonged intermittent-sprint performance either in thermoneutral or hot environmental conditions. To investigate this issue, 11 male athletes performed three trials that consisted of 80 min of intermittent-sprinting performed on a cycle ergometer, preceded by either an active or a passive warm-up. Active warm-up and intermittent-sprint performance were performed in both hot and thermoneutral environmental conditions, while passive warm-up and intermittent-sprint performance were performed in hot conditions only. First sprint performance was also assessed. Results showed no significant interaction effects between any of the trials for total work (J · kg-1), work decrement, and power decrement (P = 0.10, P = 0.42, P = 0.10, respectively). While there were no significant differences between trials for work done for first sprint performance (P = 0.22), peak power was significantly higher after passive warm-up compared with active warm-up performed in either thermoneutral (P = 0.03) or in hot conditions (P = 0.02). Results suggest that the main benefits of warm-up for first sprint performance are derived from temperature-related effects. Active warm-up did not impair prolonged intermittent-sprint performance in the heat compared with thermoneutral conditions.